2014
DOI: 10.1111/ppl.12250
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐stress induced modulation of chlorophyll biosynthesis during de‐etiolation of rice seedlings

Abstract: Chlorophyll biosynthesis in plants is subjected to modulation by various environmental factors. To understand the modulation of the chlorophyll (Chl) biosynthesis during greening process by salt, 100-200 mM NaCl was applied to the roots of etiolated rice seedlings 12 h prior to the transfer to light. Application of 200 mM NaCl to rice seedlings that were grown in light for further 72 h resulted in reduced dry matter production (-58%) and Chl accumulation (-66%). Ionic imbalance due to salinity stress resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 71 publications
4
56
0
Order By: Relevance
“…The regulated key enzymes in this pathway are 5-aminolevulinic acid (ALA) dehydratase (EC-2.4.1.24), porphobilinogen deaminase (EC-2.5.1.61), coproporphyrinogen III oxidase (EC-1.3.3.3), protoporphyrinogen IX oxidase (EC-1.3.3.4), Mg-protoporphyrin IX chelatase (EC-6.6.1.1) and ferrochelatase (EC-4.99.1.1). These enzymes are nuclear-encoded, but the pathway is located in chloroplasts and mitochondria, and they are important for biosynthesizing chlorophyll and heme in plant leaves [8]. Genes encoding these six enzymes are alaD , pbgD , cpo , ppx , chlD and fch , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The regulated key enzymes in this pathway are 5-aminolevulinic acid (ALA) dehydratase (EC-2.4.1.24), porphobilinogen deaminase (EC-2.5.1.61), coproporphyrinogen III oxidase (EC-1.3.3.3), protoporphyrinogen IX oxidase (EC-1.3.3.4), Mg-protoporphyrin IX chelatase (EC-6.6.1.1) and ferrochelatase (EC-4.99.1.1). These enzymes are nuclear-encoded, but the pathway is located in chloroplasts and mitochondria, and they are important for biosynthesizing chlorophyll and heme in plant leaves [8]. Genes encoding these six enzymes are alaD , pbgD , cpo , ppx , chlD and fch , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The first four genes encode enzymes involved in biosynthesis in chloroplasts, while last two enzymes act in directing the pathway towards heme biosynthesis in both chloroplasts and mitochondria. The two tetrapyrroles (chloroplast and heme) are important for plant growth and development, especially under abiotic stresses [8]. The Mg-chelatase enzyme was also reported to respond to changing environments [8].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3a). The lowering of chlorophyll content is possibly due to the disrupted photosynthetic machinery and decreased activities of different enzymes reported by Turan and Tripathy (2015) in rice seedlings. Amirjani (2011) and Rao et al (2013) also observed the degradation of leaf chlorophyll a, b and total chlorophyll content after NaCl treatment in rice.…”
Section: Discussionmentioning
confidence: 97%